International journal of web services research (IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2004)
This journal is the first refereed, international publication featuring the latest research findings and industry solutions involving all aspects of Web services technology. It covers advancements, standards, and practices of Web services, as well as identifies emerging research topics and defines the future of Web services on grid computing, multimedia, and communication. IJWSR provides an open, formal publication for high quality articles developed by theoreticians, educators, developers, researchers, and practitioners for those desiring to stay abreast of challenges in Web services technology.